Mathematical modeling of sediment-laden shallow water flow using finite volume method - Mondoñedo, Carlo Arturo San Juan
This study presents a two-dimensional hydraulic model of sediment-laden flow using finite volume method (FVM). The hydraulic equations used are the depth-integrated conservation equations of mass, momentum (longitudinal and transverse), suspended sediment, and total sediment. In the finite volume method, the mass, momentum, and suspended sediment fluxes of the conservation equations are calculated for each side of a finite volume based on an approximate Riemann problem solution.This Riemann problem solution involves approximating the fluxes by the characteristics solution of the governing equations. To solve the total sediment conservation equation, similar fluxes are generated using physically based, empirical, or semi-empirical sediment transport equations. The selection of sediment transport equation was based on field conditions